The influence of world view of optimism, perception of new vaccines, and perception of threat on Covid-19 vaccination attitude and behavior - Maryam Subandriyah; Primasatria Edastama (Universitas Aisyah Pringsewu, 2023)
Perceived vaccine effectiveness is an important vaccination attitude in determining vaccination behavior (vaccination intent, vaccination advocacy, and willingness to pay for vaccination) in terms of vaccination promotion as an effort to prevent infectious diseases. This study aims to identify the influence of world optimism (belief in the world's positivity and orderliness), perceived vaccine novelty, and perceived threats (susceptibility and severity) on attitudes and behavior related to vaccination. This research was conducted by a purposive sampling method using an online questionnaire to 160 respondents. Data analysis using Structural Equation Model (SEM) with SmartPLS software. The results found in this study were that belief in the world's positivity and orderliness did not affect perceived vaccine effectiveness. Perceived vaccine effectiveness positively affects vaccination intent and willingness to pay for vaccination but has no effect on vaccination advocacy. Meanwhile, the negative moderating effect of the perceived vaccine novelty does not affect all vaccination behavior. Perceived susceptibility significantly affects vaccination intent and advocacy but does not affect willingness to pay for vaccination. Furthermore, the perceived severity does not significantly influence all vaccination-related behavior. The managerial implication of this research for vaccination marketers and policymakers is that paying attention to several factors, namely perceived vaccine effectiveness and perceived susceptibility, will encourage people to increase vaccination-related behavior.